Low-Cost Methods for Molecular Characterization of Mutant Plants Tissue Desiccation, DNA Extraction and Mutation Discovery: Protocols - Till, Bradley J. (Springer Nature, 2015)
Plant Breeding/Biotechnology; Biological Techniques; Nucleic Acid Chemistry